Hubungan Pendidik dan Peserta Didik dalam Pandangan Filsafat Pendidikan Islam di MI Miftahut Thulab Brambang Karangawen Demak Tahun 2025 - Mujiburrohman, Mujiburrohman; Hudallah, Hudallah (Lembaga Yasin AlSys, 2025)
Islamic educational philosophy views education as a means to achieve the ultimate human goal, drawing closer to Allah, attaining wisdom, and building a just and moral society. Within this framework, educators bear the responsibility of developing the full potential of learners, affective, cognitive, and psychomotor in accordance with Islamic values. Learners, as both subjects and objects of education, require guidance to direct and cultivate their potential. The relationship between educators and learners is complementary: educators assist learners in adapting to themselves and to life’s challenges, acting as leaders, implementers of education, and members of the community; while learners actively seek, understand, and apply knowledge. This study examines the educator–learner relationship at MI Miftahut Thulab based on the principles of mutual respect, compassion, and guidance toward moral and intellectual excellence. The findings indicate that educators serve as role models and mentors, while learners actively engage in the learning process. The balance between Islamic and general knowledge is key to fostering progressive and Islamic education.